Application of Environics Color Slides in Optimizing the Health and Well-being - Sangeeth Somanadhapai; Sunil Singh Yadav; Sunita Rana (Recent Updates in Disease and Health Research Vol. 8, 2024)
Purpose: This study explores the efficacy of chromotherapy, also called Color Therapy or Visible Range Radiation Therapy, in diagnosing and potentially treating disruptions in the body’s energy chakras, which can lead to various diseases. Methodology: Chromotherapy, which uses specific uses wavelengths of visible light, was compared with phototherapy and photobiomodulation. The diagnostic tools employed included Environics Color Slides and the Lecher Antenna; an instrument based on the principle of resonance. The results were compared with those from the Es-Teck Complex (LD Technology US), an FDA-approved medical software and machine. Results: The comparison between the diagnostic results from the color slides and the lecher Antenna with those from the Es-Teck Complex demonstrated a correlation in identifying color deficiencies related to the chakra disruptions. Conclusion: The findings suggest that chromotherapy could be a viable non-pharmacological therapeutic modality for diagnosing and addressing energy imbalances. Future studies are needed to validate the durability and efficacy of this healing technique.